Implementasi Layanan Bimbingan Kelompok dengan Teknik Role Playing untuk Meningkatkan Self Convidence Siswa Sekolah Menengah Atas - Hamka, Raoda; Suarja, Septya; Pribadi, Imam (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
This research aims to increase self-confidence (self-confidence) students of SMA Negeri 10 Luwu through group guidance services with techniques role playing. The method used was classroom action research (PTK) which was carried out in two cycles. Each cycle consists of planning, implementation, observation and reflection stages. The subjects of this research were 10 class XI students who were identified as having self-confidence low. The research results show that the implementation of group guidance services using techniques role playing effective in improving self-confidence student. Students begin to show courage in expressing opinions, active participation, and increased independence during the guidance process. Although there are several obstacles, overall the results of this study show a significant increase in self-confidence students after two cycles of implementation.